Normaalisitovaan työehtosopimukseen perustuvan paikallisen sopimisen edistäminen Kansainvälisen työjärjestön periaatteiden näkökulmasta - Lamminen, Johannes (Lakimies, 2024)
Promoting local bargaining based on a normally binding collective agreement from the perspective of the principles of the International Labour Organization The article examines the possibilities to develop local bargaining based on a normally binding collective agreement from the perspective of the International Labour Organization’s (ILO) principles for promoting collective bargaining. From the point of view of the bargaining positions of the parties, local bargaining based on a normally binding collective agreement is in the middleground between the collective bargaining of the labour market organisations and individual bargaining between the employer and the employee. Local bargaining is based on the principles of freedom of association and the right to collective bargaining, as well as the provisions that reflect them. The ILO principles for the promotion of collective bargaining emphasise the freedom and voluntariness of the procedure, the conduct of negotiations in accordance with the principles of good faith and substantive autonomy in the process of agreement. On the basis of the principles of good faith, negotiations must be conducted in a genuine and constructive spirit, aiming to reach an agreement, informing the other party of the negotiations in good time and committing to the outcome of the negotiations. From the point of view of the principles of freedom and voluntariness, it would be justifiable to start from the premise that the parties to collective agreements themselves would seek to strengthen local bargaining, for example by adding provisions or recommendations to collective agreements that concern the procedure or negotiations in local bargaining situations, which would also take into account the requirements of good faith in accordance with the principles of the ILO. In addition, there should be an assessment of the possibilities of using state mediation to resolve local disputes.